Colourless Romano-British vessel glass from the technological point of view - Stawiarska, Teresa (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2007)
Colourless glass vessels (243 objects) from Colchester are among the best studied collections. The glasses represent four groups of tableware. This paper interprets the results of physico-chemical analyses of the glass of the Colchester finds carried out by bivariant analysis and by the author’s own method (Stawiarska 1993, 2005). A comparison with Romano-British glasses from the rest of Europe and the Near East justifies the assumption that glass with high-alkaline recipes, which makes up more than 80% of the Colchester collection, was considerably different from other common Roman glass. It is likely to have originated from highly-developed workshops producing easily melting luxury glass. A comparison of the chemical features of glass from vessels from all of the groups proves that it was connected with the same manufacturing tradition of luxury glass (as regards using large amounts of alkalis and relatively pure sand, and decolouring only with antimony). The cast bowls and facet-cut beakers are more likely to have been imports from Eastern or perhaps Italian workshops. Vessels from group III were made probably and from group IV certainly in the West, the latter especially in the Rhineland (mainly Cologne)
il. ; 24 cm
Keywords: naczynia szklane rzymskie; szkło bezbarwne; analizy chemiczne; interpretacja składu chemicznego